2015
DOI: 10.1016/j.seizure.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

CSF findings in patients with anti-N-methyl-d-aspartate receptor-encephalitis

Abstract: The sensitivity of NMDA receptor antibody testing is higher in CSF compared to serum. Other CSF abnormalities are present in some patients with Anti-NMDAR-encephalitis, however these changes do not appear to affect prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 20 publications
4
62
1
1
Order By: Relevance
“…Similarly, abnormal EEG, MRI, and CSF at first disease event did not differ substantially between patients with relapsing and monophasic disease. Long‐term neurological outcome (mRS) was not affected by abnormal CSF findings in a published cohort of 43 patients, although CSF data in monophasic and relapsing patients were not provided . While these investigations did not prove useful in predicting the risk of relapse in our cohort, EEG remains a sensitive marker in the early phases of encephalitis, and the relationship between EEG features and disease severity and course is being explored closely in the recent literature …”
Section: Discussionmentioning
confidence: 84%
“…Similarly, abnormal EEG, MRI, and CSF at first disease event did not differ substantially between patients with relapsing and monophasic disease. Long‐term neurological outcome (mRS) was not affected by abnormal CSF findings in a published cohort of 43 patients, although CSF data in monophasic and relapsing patients were not provided . While these investigations did not prove useful in predicting the risk of relapse in our cohort, EEG remains a sensitive marker in the early phases of encephalitis, and the relationship between EEG features and disease severity and course is being explored closely in the recent literature …”
Section: Discussionmentioning
confidence: 84%
“…CSF findings were abnormal in most cases,19,20 albeit nonspecific 21. Lymphocytic pleocytosis and increased CSF protein was the commonest finding.…”
Section: Csf Findingsmentioning
confidence: 88%
“…75 Findings from three other studies have suggested that serum testing is less consistent, or showed antibodies in patients without anti-NMDA receptor encephalitis or immune-mediated disorders. 74,76,77 …”
Section: Approach To Patients With Clinically Recognisable Syndromesmentioning
confidence: 99%